THE QATARI EXPERIENCE IN THE NATURAL GAS INDUSTRY AND THE POSSIBILITY OF BENEFITING FROM IT IN IRAQ - Dr. Mustafa. A. Farhan; Mohammed Hussein Ali (Scholars Digest Publishing, 2023)
In the beginning it was gas, then its fruits fell on the Qataris, development, leadership, and a distinctive experience worthy of study, as Qatar turned the gas in the depths of the Gulf into a ladder that raised it to the ranks of global leadership in this industry. This advancement did not come by chance, but was serious work full of challenges, difficulties, and opportunities. Wisdom says: (Seize opportunities, for they pass over you like clouds). Qatar seized its opportunity and achieved, in record time, a successful and inspiring experience for others. Hence the idea of the research came to shed light on this experience. To benefit from it in its success story, and what it produced in the face of the challenges and obstacles it experienced, through self-reliance and benefiting from others in their participation in their technology, and thus managed a distinctive experience that was imprinted with its Qatari imprint through successful economic, administrative and technological policies. From here came the possibility of benefiting and applying appropriate Including in the Iraqi gas sector.